Pemphigoid Gestationis - literature review - Wdowiak, Krystian; Maciocha, Agnieszka; Wąż, Julia; Witas, Aleksandra; Drogoń, Justyna; Chachaj, Weronika; Słomka, Paulina; Gwóźdź, Edyta; Szymkowiak, Natalia; Gardocka, Ewa (Journal of Education, Health and Sport, 2024)
Introduction and Objective: Pemphigoid gestationis (PG) is a rare, self-limiting autoimmune disorder, typically appearing in the second or third trimester of pregnancy. It can lead to postpartum exacerbations, and studies suggest an increased risk of preterm birth and the development of Graves’ disease in the mother. The aim of this article is to gather the latest information on pemphigoid gestationis. Review Methods: A review of studies available in the PubMed database was conducted using the keywords "pemphigoid gestationis" and "dermatoses of pregnancy" in order to find publications from the last 8 years. Brief Description of the State of Knowledge: Pemphigoid gestationis (PG) is characterized by the production of IgG1 antibodies against bullous pemphigoid antigen 180 (BP180). The primary symptom of PG is intense itching, which often occurs before skin lesions develop. Diagnosis is typically confirmed through direct immunofluorescence (DIF) of perilesional skin. Treatment focuses on relieving itching and preventing new blister formation, usually starting with topical corticosteroids for mild cases, while systemic corticosteroids are reserved for more severe presentations. Recent research indicates that biologic therapies may also offer effective management options for PG. Summary: The authors highlight the need for further research due to the limited sample sizes in existing studies, as well as the potential complications during pregnancy and long-term health effects.